The impact of CSR quality on the cost of capital - LI, LU (2022)
Equity financing is an important method of financing for contemporary enterprises. The cost of equity capital has a profound impact on the production and operation activities of enterprises. Equity financing is an important method of financing for contemporary enterprises. The cost of equity capital has a profound impact on the production and operation activities of enterprises. The cost of debt capital has been widely used in the financing, investment, and capital structure decisions. Financial and non-financial information released by enterprises is indispensable for investors' investment decisions. This paper examines the question of whether CSR disclosure reduces the cost of capital and creates value for companies. Based on a review of a wide range of relevant literature and theoretical foundations, this paper proposes two main hypotheses and the corresponding regression models. Using a sample of A-share listed companies that disclosed their social responsibility reports from 2014-2018, the social responsibility report rating scores of A-shares listed companies provided by R&L Global Philanthropy Consulting (RLCCW) were used as a measure of the level of CSR information disclosure to test the research hypotheses. The study finds that a high level of CSR disclosure is conducive to a reduction in the cost of debt capital and the cost of equity capital for companies. The quality of CSR disclosure in China is low. This paper obtains empirical evidence that CSR disclosure utilizes the transmission effect of the cost of capital to influence corporate value, thereby standardizing the CSR disclosure regime and promoting corporate social responsibility. The findings of this paper have implications for relevant authorities and regulators.